Pengaruh Terapi Relaksasi Autogenik Terhadap Penurunan Intensitas Nyeri Pada Penderita Gastritis Di Puskesmas DTP Ciranjang - Ayuningsih Ayuningsih; Asep Solihat; Susaldi Susaldi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background : Gastritis is an inflammation that affects the gastric mucosa which can result in swelling of the gastric mucosa until the superficial mucosal epithelium is released which is the most important cause of digestive tract disorders, caused by irritating and infectious factors in the gastric mucosa and submucosa. The purpose of this study was to analyze the difference in reducing pain intensity in gastritis patients who received autogenic relaxation therapy. Methods: This study used quantitative research, with a quasi-experimental research design with one group pre-test and repeated measure post-test approaches. In selecting the sample used a purposive sampling method that is selected as many as 16 samples. The independent variable in this study is autogenic relaxation therapy. The dependent variable in this search is a decrease in pain intensity. Data collection in this search was carried out at the time of observation before and after each intervention was carried out. The analysis used in this study uses a non-parametric repeated measure analysis and the Shapiro Wilk normality test for respondents with a level <0.001 and a non-parametric repeated measure test P<0.05. The results showed that there was an effect of giving autogenic relaxation therapy on reducing pain intensity in gastritis sufferers at the Ciranjang DTP Health Center.